Analisa Yuridis tentang Pencalonan Kepala Daerah yang Berstatus Dua Kewarganegaraan - Ni Putu Damayanthi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2024)
In the current era of globalization and democracy, there are legal issues where regional head candidates are proven to have two citizenships, while the requirements to become a regional head candidate are Indonesian citizens as evidenced by the ownership of an ID card. There are two problems, namely How is the regulation of the nomination of the Regional Head in the Regional Head Election and How is law enforcement on the issue of nomination of Regional Heads with dual citizenship status. This research uses normative research methods. The results obtained from this research. The legal rules regarding the election of regional heads to the terms of nomination of regional heads are regulated in Law of the Republic of Indonesia Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors. Regarding one of the elected candidates who has been proven to have dual citizenship, based on the Constitutional Court Decision 135/PHP.BUP-XIX/2021, the candidate pair must be disqualified, the General Election Commission's decision is canceled and must carry out a re-vote.